'The Cros in the Markitte Stede'. The Louth Cross, its Monastery and its Town. Issue 2 (3rd July 2017) - Everson, Paul; Stocker, David
Abstract : A RECENT DISCOVERY of pieces from a major pre-Conquest cross at Louth in east Lincolnshire has prompted not just a description and assessment of the stone sculpture, but exploration of the evolution of the early monastery and town itself. It is suggested that the monument was erected as an emblematic market cross, which marked the bishop of Lindsey's mid-10th-century promotion of a market and market town at Louth, as part of his effort to re-establish himself in the region after the Viking land-taking and its English reconquest. Our analysis has wider significance than the art history of the sculpture alone, and demonstrates the potential of the large body of early stone sculpture now made more accessible through the publication of corpora in Britain.